FUBP3 regulates chronic myeloid leukaemia progression through PRC2 complex regulated PAK1‐ERK signalling. Issue 1 (7th December 2022) - Sharma, Mugdha; Anandram, Seetharam; Ross, Cecil; Srivastava, Sweta
Abstract: The development of resistance and heterogeneity in differential response towards tyrosine kinase inhibitors (TKI) in chronic myeloid leukaemia (CML) treatment has led to the exploration of factors independent of the Philadelphia chromosome. Among these are the association of deletions of genes on derivative (der) 9 chromosome with adverse outcomes in CML patients. However, the functional role of genes near the breakpoint on der (9) in CML prognosis and progression remains largely unexplored. Copy number variation and mRNA expression were evaluated for five genes located near the breakpoint on der (9). Our data showed a significant association between microdeletions of the FUBP3 gene and its reduced expression with poor prognostic markers and adverse response outcomes in CML patients. Further investigation using K562 cells showed that the decrease in FUBP3 protein was associated with an increase in proliferation and survival due to activation of the MAPK–ERK pathway. We have established a novel direct interaction of FUBP3 protein and PRC2 complex in the regulation of ERK signalling via PAK1. Our findings demonstrate the role of the FUBP3 gene located on der (9) in poor response and progression in CML with the identification of additional druggable targets such as PAK1 in improving response outcomes in CML patients.